1990
DOI: 10.2172/6570377
|View full text |Cite
|
Sign up to set email alerts
|

The production and certification of a plutonium equal-atom reference material: NBL CRM 128

Abstract: This reportwas preparedas an accountof work_-_nsorcdby an agcncyof the UnitedStates Government.Neither the United StatesGovernmentnorany agencythereof,norany of their employees, makesany warranty, expressor implied,or assumesany legal liabilityor responsibility for the accuracy,complctcness, or usefulnessof any information, apparatus, product, or processdisclosed,or representsthat its use wouldnot infringeprivatelyownedtights,Rcfcr-cnc¢hereinto any specificcommercial product, process,or serviceby tradename,tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Attempts were made to identify, eliminate, reduce, or control probable sources of systematic uncertainty attributable to instrumental factors. 1,2 Through systematic studies it was demonstrated that, for isotope ratio measurements by TIMS, even when uncertainty contributions from chemistry and instrumental factors were negligible, signicant biases were possible because of differences in the sample mounting or the pattern of lament heating. The NBS measurement approach was: evaluate the degree of constancy of the isotopic ratio bias under various operating conditions, the best set of conditions (in terms of smaller absolute magnitude of the bias and its variability) were adopted for analyses, the constancy of the bias was veried using standards of known isotopic composition, and the same bias correction was applied on the unknown samples.…”
Section: Nbs Analytical Methods For Characterization Of Crmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Attempts were made to identify, eliminate, reduce, or control probable sources of systematic uncertainty attributable to instrumental factors. 1,2 Through systematic studies it was demonstrated that, for isotope ratio measurements by TIMS, even when uncertainty contributions from chemistry and instrumental factors were negligible, signicant biases were possible because of differences in the sample mounting or the pattern of lament heating. The NBS measurement approach was: evaluate the degree of constancy of the isotopic ratio bias under various operating conditions, the best set of conditions (in terms of smaller absolute magnitude of the bias and its variability) were adopted for analyses, the constancy of the bias was veried using standards of known isotopic composition, and the same bias correction was applied on the unknown samples.…”
Section: Nbs Analytical Methods For Characterization Of Crmsmentioning
confidence: 99%
“…SRM 996, plutonium-244 spike assay and isotopic standard, was characterized in 1981 and the equal-atom Pu CRM 128 was characterized by NBL in 1990. 2,22 Mass bias correction for SRM 996 was based on measurements of SRMs 947 and 948 analyzed concurrently with the characterization aliquots of SRM 996. For CRM 128, the correction for mass bias effects was based on gravimetric mixtures prepared using high-purity Pu isotopic end-members.…”
Section: Nbs Analytical Methods For Characterization Of Crmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, it was assumed that plutonium exhibits a mass bias comparable to uranium isotopes during the evaporation process in the thermal ion source. Thus, SRM 946–948 were certified employing the mass bias factor calculated using uranium isotopes. The fractionation factor derived from the TIMS analysis of the aforementioned certified isotope ratios was subsequently employed for mass bias correction in the later prepared plutonium standards, specifically SRM 947 and 948 for SRM 996 and SRM 946 and SRM 948 for CRM 122. In contrast, mass bias estimation for plutonium isotope ratios in CRM 128 involves measuring gravimetric mixtures of highly enriched uranium isotopes alongside standard plutonium solutions. In summary, the correction of mass bias for plutonium isotope ratios in the certification of isotopic standards depends upon assuming a parallel bias with uranium isotopes during the evaporation process in the thermal ion source.…”
Section: Introductionmentioning
confidence: 99%